Iminopyrimidinones: A novel pharmacophore for the development of orally active renin inhibitors. Issue 7 (1st April 2015) - McKittrick, Brian A.; Caldwell, John P.; Bara, Thomas; Boykow, George; Chintala, Madhu; Clader, John; Czarniecki, Michael; Courneya, Brandy; Duffy, Ruth; Fleming, Linda; Giessert, Rachel; Greenlee, William J.; et al.
Graphical abstract: The development of renin inhibitors with favorable oral pharmacokinetic profiles has been a longstanding challenge for the pharmaceutical industry. As part of our work to identify inhibitors of BACE1, we have previously developed iminopyrimidinones as a novel pharmacophore for aspartyl protease inhibition. In this Letter we describe how we modified substitution around this pharmacophore to develop a potent, selective and orally active renin inhibitor. Abstract: The development of renin inhibitors with favorable oral pharmacokinetic profiles has been a longstanding challenge for the pharmaceutical industry. As part of our work to identify inhibitors of BACE1, we have previously developed iminopyrimidinones as a novel pharmacophore for aspartyl protease inhibition. In this letter we describe how we modified substitution around this pharmacophore to develop a potent, selective and orally active renin inhibitor.